Residual pulmonary abnormalities in adult patients with chronic paracoccidioidiomycosis : prolonged observations after itraconazole therapy (2003)
ABSTRACT: Itraconazole effectively controls active paracoccidioidomycosis but appears not to hinder lung fibrosis. Clinical records and chest radiographs from 47 itraconazole-treated patients with prolonged posttherapy follow-up (mean follow-up period, 5.6 years) were analyzed; the radiographs were interpreted following pneumoconiosis standards that consider the lungs as 6 fields and grade damage according to the number of fields involved. Infiltrative lesions were observed at diagnosis in 93.6% of the patients. Fibrosis was observed in 31.8% of the patients at diagnosis and had not cleared at the end of the observation period in any of these patients. Fibrosis also developed de novo in 11 patients (25%), so that by the end of the follow-up period it was seen in 53.2% of patients overall. Fibrosis correlated with severity of infiltrates at diagnosis: fibrosis was present in 83% of patients with very severe infiltration and in 12.5% of patients with minor infiltration. Among patients with severe infiltration, fibrosis was present in 30%; this increased (to 75%) when bullae were concomitantly present at diagnosis. Prompt initiation of treatment is necessary to avoid the development of fibrosis.